PERBEDAAN PENGELUARAN ASI SEBELUM DAN SETELAH PEMBERIAN SUSU KEDELAI PADA IBU PASCA MELAHIRKAN DI RUMAH SAKIT BERSALIN FATIMAH MEDAN TAHUN 2021 (Differences in Breast Milk Secretion Before and After Giving Soy Milk to Postpartum Mothers at Fatimah Materni - Ade Lestari; Tiarnida Nababan; Fatimah Dorani; Elvi Harnista (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Fat in bosom contains an answer of protein, lactose, and natural salts that are handled by the mother's mammary organs, bosom milk is the best nourishment for children. One approach to build milk creation is by burning-through soy milk. The advantages of soy milk are to expand milk creation and increment the protein substance of soy milk by 35%. The reason for this examination was to decide the impact of giving soy milk on expanding bosom milk creation in baby blues moms at the Fatimah Maternity Home, Medan in 2021. The plan in this investigation utilized tests. A sum of 30 respondents were utilized as tests for this investigation. By utilizing the Wilcoxon grade test with a p-esteem = 0.000, it is demonstrated that giving soy milk affects expanding bosom milk creation after conveyance. The outcomes acquired from devouring soy milk influence chemicals with the aim at that the myoepithelial cells are crushed into bosom milk. This investigation concluded that there was an impact given soy milk to increase milk production in baby blues mothers. The screening recommendation is to believe that a healthy delivery can focus on nursing mothers, to be specific that utilization of soy milk is useful for bosom milk creation.